2022
DOI: 10.3390/jcm11030793
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supervised Exercise on the Development of Hypertensive Disorders of Pregnancy: A Systematic Review and Meta-Analysis

Abstract: Hypertensive disorders of pregnancy (HDP) are the most common medical complication in pregnancy, affecting approximately 10–15% of pregnancies worldwide. HDP are a major cause of maternal and perinatal morbidity and mortality, and each year, worldwide, around 70,000 mothers and 500,000 babies die because of HDP. Up-to-date high-quality systematic reviews quantifying the role of exercise and the risks of developing HDP are currently lacking. Physical exercise is considered to be safe and beneficial to pregnant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 60 publications
1
14
0
2
Order By: Relevance
“…In addition, a meta-analysis has previously demonstrated the maintenance of blood pressure values in SBP and the reduction in DBP after an AT + ST program ( Cornelissen & Smart, 2013 ). Considering that the SBP remained stable and was evidenced in a reduction in DBP, these findings are under the literature, which reaffirms the role of physical exercise in reducing the risk of disorders related to blood pressure in pregnancy ( Magro-Malosso et al, 2017 ; Du et al, 2019 ; Syngelaki et al, 2019 ; Danielli et al, 2022 ). To the best of the authors’ knowledge, there are no meta-analyses that synthesize longitudinal studies that evaluated the impacts of regular physical exercise on BP values during pregnancy.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In addition, a meta-analysis has previously demonstrated the maintenance of blood pressure values in SBP and the reduction in DBP after an AT + ST program ( Cornelissen & Smart, 2013 ). Considering that the SBP remained stable and was evidenced in a reduction in DBP, these findings are under the literature, which reaffirms the role of physical exercise in reducing the risk of disorders related to blood pressure in pregnancy ( Magro-Malosso et al, 2017 ; Du et al, 2019 ; Syngelaki et al, 2019 ; Danielli et al, 2022 ). To the best of the authors’ knowledge, there are no meta-analyses that synthesize longitudinal studies that evaluated the impacts of regular physical exercise on BP values during pregnancy.…”
Section: Discussionsupporting
confidence: 70%
“…There is evidence regarding the impacts of physical exercise on BP in pregnant women. However, there are only a few systematic reviews with meta-analyses addressing these effects during pregnancy ( Magro-Malosso et al, 2017 ; Du et al, 2019 ; Syngelaki et al, 2019 ; Danielli et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tüm gebelere sağlıklı bir diyet ve egzersizin sürdürülmesiyle ilgili genel yaşam tarzı tavsiyeleri verilmelidir. Gebelik sırasında düzenli aerobik egzersiz yapan kadınlarda hipertansif bozukluklar ve gestasyonel diyabet oranı daha düşüktür (18). ASPRE (Kanıta Dayalı Preeklampsi Önleme Aspirin) Denemesi, 11-14 haftadan 36 haftaya kadar günde 150 mg aspirin alan kadınlarda plaseboya kıyasla daha düşük preterm-preeklampsi oranı olduğu sonucuna varmıştır (%1,6'ya karşı %4,3) (19).…”
Section: Preeklempsi öNlemeunclassified
“…Significant changes in posture and shifts in centre of gravity alter maternal balance and coordination. In the past, Physical exercise is not recommended for women with high blood pressure during pregnancy because of concerns about the safety of the fetus and the pregnant woman, however, recent studies have showed that proper exercise is associated with a significantly reduced risk of gestational hypertensive disorders overall, either structured exercise or yoga have a beneficial effect for preventing the onset of pregnancy-induced hypertension (HDP) [ 9 , 15 ].…”
Section: Introductionmentioning
confidence: 99%